In Memoriam Pedro Reyes Castillo - Martínez M., Imelda; Gallina-Tessaro, Sonia; Halffter, Gonzalo (Instituto de Ecología, A.C., 2018)
Pedro Reyes Castillo, graduated from Escuela Nacional de Ciencias Biológicas of Instituto Politécnico Nacional in México. He was an important support in the formation and regular activities of the Instituto de Ecología A. C. in Xalapa, Ver. He takes part in the formation of the Biosphere Reserves in Mexico. He devoted his entire life to entomology, especially on the study of Passalidae beetles, for which he was internationally recognized. He was a great human being who loved and worked untiringly for biodiversity biology and conservation. He published more than 200 works, described many species and trained graduate students. He pass away on March 20, 2018.